Implementasi Sinergi antara Izi Jawa Timur dan Bank Permata Syariah melalui Program Lapak Berkah - Teguh Wahyudi; Arin Setiyowati (Universitas Muhammadiyah Surabaya, 2023)
The Blessing Program (Laber) is one of the forms of MSMEs needed by the community today and MSMEs themselves, including micro-enterprises, one of which is providing business capital and business facilities. The purpose of this study is to explain the implementation of the synergy between IZI East Java and Bank Permata Syariah through the lapak blessing program. The research method used is descriptive qualitative method with 2 data sources, namely primary data through observation and interviews, while secondary data sources are obtained through documentation and literature study from related references. Data analysis technique is done by data reduction, data display and conclusion drawing. The results of this study are zakat funds from the Permata Syariah bank to be managed by IZI East Java with the first stage of the mustahik submitting the program and fulfilling the requirements after that later the IZI East Java office conducted a survey related to the location and economy of his family. The office and IZI also reported related to the lapak blessing program to the Permata Syariah bank after which it would later be collected in one place for the opening of the welcoming lapak blessing program from IZI in synergy with Bank Permata Syariah, the beneficiaries will get a business capital and merchandise, such as carts, storefront and trading tools.This assistance program the community has a positive impact, one of which is being able to open a business, lapak blessing is one of the micro businesses in other words MSMEs. One of the requirements for submitting a stall for blessings is that you have to have a business for at least 1 year and there are obstacles in your business. IZI Jatim in collaboration with Bank Permata Syariah will provide capital to mustahiq (beneficiaries) to open a lapak business.